BURIED WAVEGUIDE POLYMETHYLMETHACRYLATE MODELING FOR REFRACTIVE INDEX SENSOR APPLICATION USING FINITE ELEMENT METHOD - Ian Yulianti; Jauhar Azka; Ngurah Made Darma Putra; Budi Astuti (Program Studi Fisika Universitas Negeri Jakarta, 2019)
The purpose of this study is to obtain the optimum buried waveguide structure through modeling for refractive index sensor applications. The waveguide cladding material used as Polymethylmethacrylate (PMMA). The core cross-section size was 1 × 1 mm2. The simulation was carried out at a wavelength of 650 nm using the Finite Element Method (FEM). The parameter of the buried waveguide optimized in this model was the core refractive index and the thickness of the upper cladding to obtain a high propagation constant and good sensitivity to refractive index. Modeling was done for various core refractive index values ​​varied in the range of 1.52 to 1.59, which are the refractive index of various types of polymers. To optimize the sensitivity, the thickness of the upper cladding was varied between 0.125mm to 0.5mm. Besides, a simulation was also carried out for a waveguide without an upper cladding. The results show that the optimum waveguide is a waveguide without upper cladding using polyester as core material with a refractive index value of 1.57 and a sensitivity of 4.9 × 10-10rad /m. RIU.